PENGARUH KEPATUHAN PELAPORAN KEUANGAN, SISTEM PENGENDALIAN INTERNAL DAN WHISTLEBLOWING SYSTEM TERHADAP PENCEGAHAN FRAUD PENGELOLAAN DANA DESA - Kivaayatul Akhyaar; Anissa Hakim Purwantini; Naufal Afif; Wahyu Anggit Prasetya (Faculty of Economics and Business, Universitas Warmadewa, 2022)
This study aims to empirically test the effect of financial reporting compliance, internal control systems and whistleblowing systems on fraud prevention in the management of village funds in Bansari Temanggung District. This research is a quantitative research. The source of data in this study uses primary data obtained through questionnaires. The sampling technique in this study uses purposive sampling technique, so that the research sample obtained as many as 63 respondents consisting of the village head, village secretary, treasurer, planning department and BPD in 13 villages, Bansari Temanggung District.The results of this study indicate that Financial reporting compliance and whistleblowing system have a positive effect on fraud prevention in managing village funds, temporary the internal control system has no effect on preventing fraud in the management of village funds.